Prediction of delamination of steel-polymer composites using cohesive zone model and peeling tests. (15th January 2017) - Jang, Jinhyeok; Sung, Minchang; Han, Sungjin; Yu, Woong-Ryeol
Abstract: This study reports on the prediction of the delamination of steel-polymer composites. To characterize the adhesive properties from peeling tests, a simple model was derived based on peeling mechanics, in particular considering plastically dissipated energy of polymer film due to bending. Peeling tests were performed at two angles so that the adhesive properties were determined in both normal and tangential directions. Then, peel strength at arbitrary angle was predicted and compared with experiments, showing that the peel strength at only two angles and peeling mechanics considering the bending of polymer film can accurately describe the adhesive properties of steel-polymer interface. Finally, finite element simulations based on the cohesive zone model were performed to predict the delamination between steel-polymer sandwich composites, demonstrating the validity of cohesive zone model equipped with necessary properties determined using peeling tests and the developed model in this study.